2020
DOI: 10.1111/tid.13432
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study to assess the role of polyomavirus in transplant complications: Where do we stand?

Abstract: Purpose: The study's aim was to assess whether polyomavirus DNAemia screening was associated with different outcomes in patients with positive viremia compared with negative viremia. Methods: Case-control retrospective study of patients with polyomavirus DNAemia (viremia > 1000 copies/mL) matched 1:1 with controls. Control group consists of the patient who received a transplant immediately before or after each identified case and did have nil viremia. Finding: Ultimately, 120 cases of BK polyomavirus (BKPyV) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Our findings describing risk factors associated with progression to rejection after BKPyV-DNAemia corroborate previously published data describing risk factors for rejection in the absence of BKPyV-DNAemia, including non-depleting induction immunosuppression, a higher degree of HLA mismatch, and DGF. [31][32][33] This suggests the development of BKPyV-DNAemia and resultant management do not significantly modify risk factors for rejection that are identified at transplant. As these risk factors are well known, this information reinforces our current practice of evaluating rejection risk when modifying immunosuppression in the setting of BKPyV-DNAemia.…”
Section: Ta B L E 2 Basic Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings describing risk factors associated with progression to rejection after BKPyV-DNAemia corroborate previously published data describing risk factors for rejection in the absence of BKPyV-DNAemia, including non-depleting induction immunosuppression, a higher degree of HLA mismatch, and DGF. [31][32][33] This suggests the development of BKPyV-DNAemia and resultant management do not significantly modify risk factors for rejection that are identified at transplant. As these risk factors are well known, this information reinforces our current practice of evaluating rejection risk when modifying immunosuppression in the setting of BKPyV-DNAemia.…”
Section: Ta B L E 2 Basic Demographicsmentioning
confidence: 99%
“…Recent literature suggests that the accepted practice of screening and immunosuppressive management does not improve outcomes in patients with BKPyV-DNAemia when compared to those who do not develop BKPyV-DNAemia. 33 Assays that measure immune response to BK infection and laboratory markers for BK progression could guide immunosuppressive modification and allow titration to response. In a study by Manzetti et al, BKPyV agnoprotein was identified as an important factor for immune escape and urinary shedding along with the rapid cellto-cell spread inside the renal tubules leading to the progression to BKPyVAN in KTRs.…”
Section: Ta B L E 2 Basic Demographicsmentioning
confidence: 99%